Ancient exaptation of a CORE-SINE retroposon into a highly conserved mammalian neuronal enhancer of the proopiomelanocortin gene. - Andrea M Santangelo; Flávio S J de Souza; Lucía F Franchini; Viviana F Bumaschny; Malcolm J Low; Marcelo Rubinstein (PLoS Genetics, 2007)
The proopiomelanocortin gene (POMC) is expressed in the pituitary gland and the ventral hypothalamus of all jawed vertebrates, producing several bioactive peptides that function as peripheral hormones or central neuropeptides, respectively. We have recently determined that mouse and human POMC expression in the hypothalamus is conferred by the action of two 5' distal and unrelated enhancers, nPE1 and nPE2. To investigate the evolutionary origin of the neuronal enhancer nPE2, we searched available vertebrate genome databases and determined that nPE2 is a highly conserved element in placentals, marsupials, and monotremes, whereas it is absent in nonmammalian vertebrates. Following an in silico paleogenomic strategy based on genome-wide searches for paralog sequences, we discovered that opossum and wallaby nPE2 sequences are highly similar to members of the superfamily of CORE-short interspersed nucleotide element (SINE) retroposons, in particular to MAR1 retroposons that are widely present in marsupial genomes. Thus, the neuronal enhancer nPE2 originated from the exaptation of a CORE-SINE retroposon in the lineage leading to mammals and remained under purifying selection in all mammalian orders for the last 170 million years. Expression studies performed in transgenic mice showed that two nonadjacent nPE2 subregions are essential to drive reporter gene expression into POMC hypothalamic neurons, providing the first functional example of an exapted enhancer derived from an ancient CORE-SINE retroposon. In addition, we found that this CORE-SINE family of retroposons is likely to still be active in American and Australian marsupial genomes and that several highly conserved exonic, intronic and intergenic sequences in the human genome originated from the exaptation of CORE-SINE retroposons. Together, our results provide clear evidence of the functional novelties that transposed elements contributed to their host genomes throughout evolution.